The Value Perception and Reconstruction of Cultural Heritage in Chinese City Culture Brand Design - Qi , Yichen; Sawatdee, Yodkwan (Journal of Roi Kaensarn Academi, 2024)
City image Creation requires cultural branding. The construction of an urban cultural brand first requires exploring the unique competitiveness of the city itself. The uniqueness of a specific nation, regional history, cultural tradition, and lifestyle reflected in cultural heritage plays an irreplaceable role in shaping urban cultural brands. However, constructing urban cultural brands with cultural heritage resources has a single dimension of value recognition and meaning interpretation. To better upgrade the work of cultural heritage protection to urban image and shape urban cultural brand, the study proposes from the perspective of meaning-driven innovation in the design field by changing the cognitive context of cultural heritage, broadening the cognitive dimension of value, and optimizing the communication space. To redefine the contemporary significance of cultural heritage; to reconstruct the relationship between cultural heritage and urban cultural brand design from the perspectives of local environment, cultural context, experience interaction, etc.; to explore and obtain urban discourse from the diachronic and immediacy aspects of cultural heritage resources right path. The research conclusions are as follows: it affirms the importance of cultural heritage in constructing urban cultural brands, recognizes and reconstructs its value through methods such as transforming time and space context, and shapes the urban artistic image. This study provides valuable insights into the interactions between cultural heritage, urban development, and urban culture in China.